Student Character Development: How Do Buddhist Religious Retreat Activities Matter to Students’ Discipline at Schools? - Epi Epi; Wiastina Seneru; Juni Suryanadi; Sidartha Adi Gautama; Dittha Winyana Putra (Universitas Sebelas Maret, 2024)
This study aimed to find the Influence of Buddhist Religious Retreat Activities on Student Discipline. The problems that occur in students are the lack of awareness of students to maintain a learning atmosphere, low student responsibility for assignments, lack of understanding of students to sustain social interaction ethics, and lack of student participation in school activities. This study uses a quantitative approach with a survey method. The population in this study was 89. The results showed that retreat activities positively and significantly influenced student discipline, with a t-value of 3.446 and a significance (p) of 0.001 <0.05. This indicates that retreat activities do have a positive effect on student discipline. Based on a simple linear analysis, the R square value of 0.120 suggests that retreats contribute 12.0% to discipline, while the other 88.0% is influenced by different factors, such as the school environment, family, and peers. This confirms that retreat activities are only one component in forming discipline, while other factors outside of spiritual activities also have an essential role in creating the character and self-development of students.